(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Ensérune (Nissan-lès-Ensérune, Hérault, France) is a major archaeological site for studying linguistic exchanges in the preroman iberian north area. This paper presents the celtic names read in palaeohispanic ins- criptions and to sets them back in their archaeological context. This essay in methodology provides an examination of and precise examples for Javier de Hoz’s hypothesis of iberian as a lingua franca.